The Impact of Using the Vote Recapitulation Information System (SIREKAP) Application on the Vote Recapitulation Process in the 2024 Election (Case Study of the Tangerang City General Election Commission) - Rizkyka Rahma Danti; Hilman; Muhammad Ibrahim Rantau (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Impact of Using the SIREKAP Application on the Vote Recapitulation Process in the 2024 Election (Case Study of the Tangerang City General Election Commission). With the post-2024 election phenomenon, SIREKAP remains a significant challenge in implementing technology in a democratic system, particularly with regard to data accuracy, information transparency, the readiness of facilities and infrastructure, and workforce readiness. The purpose of this study is to analyze the recapitulation system and the policy impact of using the SIREKAP application on the vote recapitulation process in the 2024 Legislative Election in Tangerang City. This study used qualitative research methods. Data were collected using observation, interviews, and documentation techniques. The types and sources of data were primary and secondary data. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The research location was the Tangerang City General Election Commission. The theoretical concept used was the Policy Impact Indicator (Dye, 1975), which focuses on five indicators: impact on target groups, impact on non-target groups, current and future impacts, direct cost impacts, and indirect impacts. Based on the research results, it can be concluded that the 2024 Election results recapitulation system, which combines traditional manual methods with digital technology (SIREKAP), has demonstrated complex and diverse effects. Although SIREKAP was launched to increase effectiveness and transparency, it has been found to disrupt operations by increasing the workload of officers, leading to the spread of misinformation, and reducing public trust. Keywords: Policy Impact, SIREKAP, Tangerang City Election Commission (KPU).